Evaluasi Kebijakan Penyelenggaraan Perparkiran dalam Meminimalisir Parkir Liar di Kota Surabaya Provinsi Jawa Timur - Wisna Junita Lase; Joko Widodo; Radjikan Radjikan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research was conducted with the aim of evaluating parking management policies in minimizing illegal parking in the city of Surabaya. This research analysis was carried out using a qualitative descriptive approach. The research results show that the parking policy in the city of Surabaya has been implemented and implemented in stages, but this is still less effective in overcoming the problem of illegal parking in the city of Surabaya. In minimizing illegal parking in the city of Surabaya, the government must pay close attention and understand the obstacles faced by the community, improve the quality of parking services and optimize the use of parking lots and also reduce the number of illegal parking perpetrators.